Histological Study of the Intestine of Stoliczkae’s Barb Puntius stoliczkanus (Day, 1871) (Cypriniformes: Cyprinidae) - Senarat, Sinlapachai; Yenchum, Watiporn; Poolprasert, Pisit (Agriculture and Natural Resources, 2013)
The histological and histochemical characteristics of the digestive tract of Stoliczkae’s barb Puntius stoliczkanus (Day, 1871) were examined. This fish had an intermediate gut length with the nonexistence of the stomach. The histology revealed that the intestine consisted of four different layers: mucosa, submucosa, muscularis and serosa. The mucosa comprised the various villi and simple, columnar epithelia which were lying on the lamina propria. Muscularis mucosae and mucosal tubular glands were not present. Eosinophilic granular cells were observed along the intestine, mainly beneath the lamina propria. Histochemical analysis showed the goblet cells and eosinophilic granular cells react positively with periodic acid-Schiff. This research reports on the histological study of the alimentary tract of P. stoliczkanus for the first time.